Finding Clara: Establishing the Biographical Details of Clara Peeters (ca. 1587–after 1636) - Jean Bastiaensen (Boletín del Museo del Prado)
This article is the first to shed light on the life of Antwerp painter Clara Peeters. Analysis of the existing literature and studies of untapped archival pieces led to the discovery that Clara Peeters could be one Clara Lamberts, born into the third generation of a family of painters in Mechelen around 1587, and later becoming the wife of the painter Henrick II Peeters. The author has found possible evidence that her studio may have been in Antwerp, where she painted the majority of her works. Clara Peeters-Lamberts most likely died in Ghent sometime after 1636.